Mulher não vale nem um real : patriarcado nas letras das músicas de forró - Feitosa, Sônia de Melo (2011)
Patriarchy is a dominating system that establishes male power in social relations as the social-ideological system and the structuring element of several ways of men‟s domination on gender social relations, on organization of social life, on private relations, and on political decision spaces. In this study we enlarge our reflection about patriarchy from the analysis of Forró lyrics, more specifically the variation known as stylized. Of late decades, it is a kind of music that has been receiving a large acceptance all over the national territory, making use of everyday expressions that propagate and make apology to many forms of discrimination, oppression and violence against women. We emphasize that over this study 14 Forró lyrics were analyzed of different styles besides stylized, like the traditional and the double meaning ones. However, we dwelled on the content analysis, particularly in three Stylized Forró lyrics, they are: Tapa na Cara (2008) by Saia Rodada Band; Mulher Roleira (2004), Aviões do Forró Band; and Bomba no Cabaré (2007), Matruz com Leite Band. In order to make a critical analysis of the elements in the lyrics content, we support ourselves on the theoretic-methodological references of the dialectical materialism, a method that allowed us to get closer to the totality of the reality that includes the popular involvement of the analyzed lyrics in a qualitative way. In that sense, we hold onto the theoretic-methodological categories: gender social relations, patriarchy, violence against women, ideology and cultural industry. As from the lyrics compilation, they were arranged by theme, we classified and analyzed the content, which allowed us to comprehend the messages in the lyrics, beyond the text shows at first sight. Today, there are many mechanisms of propagation and perpetuation of patriarchal ideology. A very relevant mechanism of this phenomenon is the sexual violence. The violence against women is a form to propagate and keep sexism, which may occur in different ways, like physical, psychological, sexual, patrimonial and social. Through our study we established that the propagation of the violence against women as being something natural and banal, giving reinforcement to the asymmetric construction of gender relations that priorizes male to the detriment of female. This banalization is perhaps, one of the strongest allies of this phenomenon‟s perpetuation, that affects women all over the world from different social classes